Estudo farmacologico do extrato etanolico da entrecasca da Caesalpinia pyramidalis Tul. (Leguminosae) - Santos, Cliomar Alves dos (2010)
Inflammation is an important component of many diseases whose core process is the phagocytic cell recruitment causing tissue damage. Plants with therapeutic use by the population are alternatives for the treatment of inflammatory diseases, among them Caesaplinia pyramidalis is popularly known as "catingueira", and the objective of this study is to investigated the anti-inflammatory, antinociceptive and antioxidant activities of the ethanol bark extract (EBE) of this semi-arid Northeast plant. The preliminary phytochemical screening of the EBE revealed the presence of the following classes of secondary metabolites: phenols, tannins, flavonoids, steroids, triterpenes, and saponins. Animals were pretreated with the EBE of C. pyramidalis (100, 200, and 400 mg/kg, p.o.) or vehicle (0.2% tween 80 in saline, 10 mL/kg, p.o.) 1 h before. Separate groups of animals were pretreated 1 h before with acetylsalicylic acid (ASA, 300 mg/kg, p.o., for writhing, formalin and paw edema tests), dexamethasone (2 mg/kg, s.c., for model of peritonitis and paw edema) or naloxona (5 mg/kg, i.p., for hot plate test) and 30 min before with morphine (3 or 10 mg/kg, i.p., for hot plate test and formaline test) or diazepam (1,5 mg/kg, i.p., for rota rod test) which were used as standard controls. To assess the antinociceptive activity we have used the acetic acid-induced writhing (0.6%, 0.1 mL/10g, i.p.), formalin (2%, 20 μL/paw) or hot plate models in Swiss mice (n = 6/group). The EBE, at the doses of 100, 200, and 400 mg/kg, significantly reduced (P < 0.001) the abdominal writhing in 20.9, 41.7, and 69.5%, respectively, as compared to control (31.17 ± 0.95 writhes). The extract at the doses of 100, 200 and 400 mg/kg decreases significantly the time that animals spent licking/bitting their paw during both phases of the formalin test (P < 0,05) and increased the latency of animals in the hot plate test in recorded times (P < 0,05), as well as morphine efect. Naloxone was capable of reversing the inhibition evoked by the EBE (400 mg/kg) on the hot plate model, as well as the morphine effect. In order to exclude a possible involvement in motor activity of the extract was performed to rota-rod test in which the results showed no statistical difference with the group that received vehicle. To evaluate the anti-inflammatory activity were used in vivo models of paw edema and peritonitis. In the paw edema model induced by 1% carrageenan (100 μL/paw, s.c.) in Wistar rats (n = 6/group), the EBE of C. pyramidalis at the dose of 400 mg/kg caused inhibition of 41.2% in the edema formation (P < 0.05). The recruitment of neutrophils to the swollen paw was indirectly measured by determining the MPO activity. Oral treatment of the animals with the EBE of C. pyramidalis (400 mg/kg) was able to reduce in 37.1% MPO 12 activity when compared with control (7,12 ± 0,94 UMPO/mg tissue, P < 0.05). In the peritonitis model in Swiss mice (n = 6/group), 4 h after injection of carrageenan (1%, 0.25 mL, i.p.), was observed that the EBE inhibited (P < 0.01) the leukocyte migration into the peritoneal cavity in 58,6% at the dose of 400 mg/kg, as compared to control (7,22 ± 0,99 x 106 leukocytes/mL). The differential count of leukocytes confirmed the decrease (P < 0.001) of the polymorphonuclear cells to the inflammatory site at the doses of 200 and 400 mg/kg. The antioxidant test used was the lipid peroxidation by thiobarbituric acid reactive species (TBARS) where an in vitro system of radical production (AAPH-2,2-azobis-2- metilpropionamidina) evaluated the EBE ability (1 - 1000 μg/mL) to modulate oxidative damage in a preparation of liposomes, using vitamin C (1.76 μg/mL) as control. The concentrations of the 100 and 1000 μg/mL of the EBE of C. pyramidalis reduced (P < 0.01) TBARS production, which strengthens the relationship between anti-inflammatory activity and antioxidant compounds. Concludes that the plant Caesalpinia pyramidalis has antiinflammatory, antinociceptive and antioxidant activities, supporting the use in popular medicine as anti-inflammatory agent. These biological activities may be related, at least in part, to the presence of tannins, flavonoids, and saponins.